Dentoalveolar Fracture with Mild Head Injury ; A case report - Tajrin, Andi; Ruslin, muhammad; Fauzi, Abul; Rasul, Muhammad I.; Gazali, Moh.; Nurwahida, Nurwahida; Ariestiana, Yossy Y. (Journal of Case Reports in Dental Medicine, 2020)
Introduction:Â Trauma to the teeth and its supporting tissues often occurs in trauma patients. The involvement of orofacial trauma is estimated to be around 15% of all emergency patients, and 2% of these cases involve dentoalveolar trauma.Objective: Case report of a 53-year-old man case of gum, with complaints of tooth, gum, and head pain due to trauma from motorcycle accidentCase Report: Complaints experienced by a single motorcycle accident and hit a wooden board with the position of the face hit first, patients have lost consciousness shortly after the accident. Complaints of pain in the upper lower lip and gum, avulsion on teeth 11,21 and mobility on teeth 12,22,31,32,41,42.Discussion: The patient had previously treated in a community health service so that the airway inspections and handling were not carried out. Observative was carried out in consultation with the Neurosurgery section for a history of loss of consciousness, than the definitive care by attaching an Eyelet splint for a fixation to the maxillary anterior teeth, and fixation with Erich arch bar for the mobile mandibular anterior teeth. These actions was performed under general anesthesia.Conclusion:Â Interdental Wiring (IDW) is an intraoperative fixation technique for dentoalveolar trauma, in this case eyelet splints and Erich arch bar were used. Patients with head trauma should be consulted to Neurosurgery department before the definitive treatment.